The Influence of Taxpayer Moral Obligations, Taxpayer Financial Conditions, and Tax Sanctions on Taxpayer Compliance in Paying Motor Vehicle Taxes (Study at the South Surabaya Samsat Joint Office) - Muslimah, Aprilia; Widajantie, Tituk Diah (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
Taxes are obligatory payments to the state that can be imposed on individuals who are required to pay them following rules without receiving any kind of reimbursement. These taxes can be directly assigned to the state and are used to fund general expenses associated with the government's operations. The annual increase in motor vehicles may affect taxpayer compliance. The purpose of this study is to ascertain how taxpayer compliance concerning paying motor vehicle taxes is impacted by taxpayer moral obligations, taxpayer financial circumstances, and taxpayer sanctions. This study employed Structural Equation Modeling Partial Least Square (SEM PLS) analysis as a data analysis technique. Purposive sampling, which implies selecting samples to look at certain factors first, is a non-probability sampling strategy used in this study. In this study, there were 19 (indicators) x 100 = 1900 respondents, or samples. Findings from this study indicate that while financial conditions do not significantly affect taxpayer compliance, taxpayer moral obligations, and tax sanctions do have a considerable positive impact.